Cost-effectiveness of anti-hypertensive medications in a regional hospital in rural Malaysia - Mohd Shah, Azarisman Shah; Ngow, Harris Abdullah; O, Marzuki; A.M., Puteri Melor; Ab Rahman, Jamalludin; Mohamed, Sahimi; Satwi, Sapari; S, Noorfaizan; Maskon, Oteh (Wolters Kluwer, 2008)
Objectives: Hypertension is one of the most important risk factors for Cardiovascular Disease in Malaysia. Population-based hypertension control is extremely poor at only 6% based on the 1996 National Health and Morbidity Survey. One of the possible reasons include the availability and cost of antihypertensive medications. Methods: A retrospective review of the annual cost (2006) of anti-hypertensive medications was undertaken at the Department of Pharmacy, Hospital Tengku Ampuan Afzan, a 600-bed major regional hospital on the east-coast of Malaysia. The total number of prescriptions given out and the total cost per drug is then factored to give the annual cost per drug per person in a percentage of the total annual expenditure. Results: The majority of patients were on either 2 (46.5%) or 3 (25.9%) anti-hypertensives. The most frequently prescribed medications were ACE-Inhibitors (33.45%), Calciumchannel blockers (29.63%), diuretics (16.67%), Beta blockers (13.64%) and Alpha blockers (2.69%). In terms of cost however, the Calcium-channel blockers constituted the greatest percentage of the annual anti-hypertensive budget (63.67%) compared to ACE-Inhibitors at just 20.04% of the annual expenditure. The most ‘cost-effective’ group of drugs are the diuretics making up 16.67% of the total annual prescriptions but only constituting 1.23% of the annual cost. Conclusion: The Calcium-channel blockers are the most ‘cost-ineffective’ medications available at our regional Hospital making up less than one third of the total annual prescriptions but making up nearly two-thirds of the annual anti-hypertensive budget. The most ‘cost-effective’ medications were diuretics, Beta-blockers and ACE-inhibitors in order of ‘cost-effectiveness’.